Antibodies against p53 protein (anti-p53 Ab) - Bigda, Jacek; Dobrzańska-Paprocka, Zuzanna (Contemporary Oncology/Współczesna Onkologia, 2003)
The gene coding p53 tumor suppressor protein is the most often damaged gene in human cancer cells. Serum antibodies against p53 protein are observed in 30 to 40% of patients with mutated p53 gene. The antibodies belong most frequently to IgG1 and IgG2 subclasses. The crucial role in the development of the anti-p53 humoral response is attributed to a prolonged half life of altered p53 protein and cellular accumulation of that protein. There are no well defined reasons why the major group of patients with damaged p53 gene does not produce antibodies against p53 protein. Anti-p53 Ab are hardly ever present in healthy controls (frequency below 0.5%) and are considered to be a tumor marker. In the case of some cancer types the presence of serum antibodies against p53 protein can be a negative prognostic factor. Furthermore, studies on populations at high risk of cancer demonstrated the appearance of antibodies against p53 protein several months before the clinical diagnosis of cancer. Determination of anti-p53 Ab and panel of other antibodies against tumor associated antigens in the patient’s serum is a promising way to early cancer detection and improvement of treatment results.